Some new exact solutions for derivative nonlinear Schrodinger equation with the quintic non-Kerr nonlinearity - Korpinar, Zeliha; İnç, Mustafa; Bayram, Mustafa (World Scientific Publ Co Pte Ltd, 2020)
The extended generalizing Riccati mapping method (EGRM) is used to solve the derivative nonlinear Schrodinger equation (DNLSe) with the dimensionless shape. This method reveals several optical solitons including traveling wave solutions (TWS). The studied solutions are identified in four different families including the hyperbolic, the rational and the trigonometric functions. Evaluations of the method are presented with graphical results obtained from our solutions.
Keywords: TWS; derivative nonlinear Schrodinger equation; EGRM